Inhibition of prolyl hydroxylases by dimethyloxaloylglycine after stroke reduces ischemic brain injury and requires hypoxia inducible factor-1α - Ogle, Molly E. (2011)
Pathological oxygen deprivation inhibits prolyl hydroxylase (PHD) activity and stimulates a protective cellular oxygen-sensing response in part through the stabilization and activation of the Hypoxia Inducible Factor (HIF) 1α transcription factor. The present investigation tested the therapeutic potential of enhanced activation of oxygen-sensing pathways by competitive pharmacologic PHD inhibition after stroke, hypothesizing that post-ischemic PHD inhibition would reduce neuronal cell death and require the activation of HIF-1α. The PHD inhibitor dimethyloxaloylglycine (DMOG, 100μM) reduced cell death by oxygen glucose deprivation (OGD), an in vitro model of ischemia, and the protection required HIF-1α. In vivo, DMOG (50mg/kg, i.p.) administered 30 or 60 min after distal occlusion of the middle cerebral artery (MCA) in mice enhanced the activation of HIF-1α protein, enhanced transcription of the HIF-regulated genes vascular endothelial growth factor, erythropoietin, endothelial nitric oxide synthase, and pyruvate dehydrogenase kinase-1, reduced ischemic infarct volume and activation of the pro-apoptotic caspase-3 protein, reduced behavioral deficits after stroke, and reduced the loss of local blood flow in the MCA territory after stroke. Inhibition of HIF-1α in vivo by Digoxin or Acriflavine abrogated the infarct sparing properties of DMOG. These data suggest that supplemental activation of oxygen-sensing pathways after stroke may provide a clinically applicable intervention for the promotion of neurovascular cell survival after ischemia.